(untitled) - Nguyễn, Xuân Thắm (Cần Thơ, 2011)
This research aimed at exploring cognitive learning styles preferred by students in the two different academic major fields in learning English as a foreign language. This paper also reported on a comparison of students’ learning style preferences with their learning style practices.
Keywords: Learning style,Phong cách học thuật